Pengaruh Vegetasi di Perkebunan Kopi Robusta terhadap Keanekaragaman Kumbang Tanah (Ground Beetle) - Kunni Lailatus Salamah; Nanang Tri Haryadi; Gracia Melsiana Aldini; Agung Sih Kurnianto; Nilasari Dewi (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2023)
Coffee cultivation is inseparable from the threat of pests and diseases. This problem became a polemic that until now has yet to be resolved properly. Chemical control using pesticides that farmers have carried out makes pests more resistant. Pest control on coffee plants can utilize insects that act as predators, like the ground beetle. This research was conducted at the Experimental Garden of the Indonesian Coffee and Cocoa Research Institute, the Agrotechnology Laboratory, and The Laboratory for Pest and Plant Disease Protection at the Indonesian Coffee and Cocoa Research Center from October 2022 to February 2023. Sampling was done by purposive sampling using the pitfall trap method. The results are then calculated in the importance value index, diversity index, dominance, and evenness. Researchers also analyzed the relationship between vegetation at the study site and the diversity of ground beetles found by vegetation types present at the study site and calculated the value of each ecological index including diversity, dominance, evenness, and importance value indexes. Kaliwining experimental garden, the acquisition of ground-level arthropods obtained a high score with a diversity level of 1.333, and for the Wirolegi experimental garden 0.975.